The Effect of Local Wisdom-Based Wayground Media on Fraction Problem-Solving Skills in Primary School - Waliah, Diyah Rutin; Suciptaningsih, OKtaviani Adhi; Mardhatillah (IKIP Siliwangi, 2026)
Mathematics education in elementary schools often encounters challenges, especially in teaching fractions that are many students difficult to understand it. These challenges need for more interactive and contextual teaching methods that can improve students' comprehension of fractions. The purpose of study to evaluate the effectiveness of Wayground media based on local wisdom, in increasing fraction problem-solving skills in primary school students. The Method of research employed a quantitative pre-experimental design with a one-group pretest and posttest, conducted on fifth-grade students at SD Islam Sabilillah Malang. Instruments based on Polya's problem-solving indicators were used to measure students’ abilities, beside their validity and reliability were tested using Cronbach's Alpha. Additionally, a questionnaire was administered to assess student responses to the Wayground media. Data analysis was performed using Microsoft Excel, including normality tests and calculation of the N-Gain Score. The results indicated a significant improvement in students' problem-solving skills, with pretest scores averaging 42.57 and posttest scores increasing 74.77. The N-Gain score of 0.5573 placed the media in the